Pelatihan Pembuatan Kerajinan Tangan Dari Kain Perca Dan Kain Flannel Guna Meningkatkan Kreativitas Anak Tpq Miftahul Huda Jatisari - Wifqiatul Izzah; Miksan Ansori (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2021)
Training activities for making handicrafts from patchwork and flannel cloth in TPQ Miftahul Huda children are trying to provide child skills training, sharpen fine motor, accuracy, patience, while sharpening children's brains to improve their creativity. In addition, making handicrafts also trains children to develop self-confidence. They can show their work to friends, family and parents. It illustrates their confidence that began to form through the results of work. Children's creativity will also grow and also increase through this activity. This activity can also be a new activity for children, so that they do not only play gadgets and games, so the researcher's work program is training in making handicrafts from patchwork and flannel cloth to improve children's creativity. This activity is to fulfill their creation and imagination by creating a skill that is expected to increase the creativity of TPQ children during the current pandemic.